Analisis Tingkat Pelayanan Jalan Dan Evaluasi Struktur Perkerasan Jalan Pada Jalan Semeru, Jalan Pancasila Dan Jalan Kolonel Sudiarto - Mirajhusnita, Isradias; Yusuf , Muhammad; Yunus, Muhamad; Ayu Nisya’ul Fitri, Ros (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2021)
Tegal city station which is in the center of Tegal city. Activities in and out of station visitors lead to a density of road capacity. As well as the smoothness of traffic also depends on the condition of the road pavement. This study aims to determine the level of road service and evaluation of road pavement thickness as well as to provide alternative ways of handling road problems on Jalan Semeru, Jalan Pancasila and Jalan Kolonel Sudiarto which are influenced by road users around the Kota Tegal station. The benefits of the research provide material for consideration of regional structuring policies and input data on road improvement planning for related agencies. The research method is qualitative, namely analyzing the level of road service with LOS calculations according to the 1997 Indonesian Road Capacity Manual and evaluating pavement thickness with CESA calculations according to the 2013 Road Pavement Design Manual. Data analysis was obtained from field measurements and traffic volume calculations. The results of the calculation of the analysis of the level of road service on Jalan Semeru, Jalan Pancasila and Jalan Kolonel Sudiarto are at service level C, namely stable current conditions with an average speed of 30 km / h due to side obstacles so that the driver has limitations in choosing speed, it is recommended to add and traffic sign confirmation. Evaluation of the structure of the pavement layer on Jalan Pancasila is adequate for the next 20 years of planning life. Meanwhile, Jalan Semeru with a length of 610 meters and a width of 550 meters as well as Jalan Kolonel Sudiarto with a length of 845 meters and a width of 700 meters need to be thickened with a layer of wear layer (AC-WC) with a thickness of 4 cm at a cost of Rp. 1,256,137,000.